Peningkatan Kapasitas Aparatur Desa melalui Pelatihan Perencanaan Pembangunan dan Tata Kelola Administrasi Desa di Kecamatan Namorambe - Piki Darma Kristian Pardede; Apriliani Lase; Doli Tua Mulia Raja Panjaitan; Prietsawenny Riris T Simamora (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
This community service initiative aimed to facilitate training in the field of village administration, with the objective of enhancing village development planning and strengthening digital-based village administrative governance. Through this program, it was expected to foster accountable and transparent governance at the village level and to develop village officials with comprehensive knowledge, positive attitudes, and proficient skills conducive to advancing village development. The community service activities were conducted from 26-28 August 2024 and involved 4 lecturers, 6 officials from the Namo Tualang Village Government, and 15 members representing both the local community and the Village Consultative Body (BPD). Meanwhile, activities in Gunung Kelawas Village involved the village head, 4 village officials, 4 of BPD, and 7 community representatives. The methodologies employed in this initiative were Participatory Rural Appraisal (PRA) and Participatory Learning and Action (PLA). The activities focused on lectures, discussions, and interactive brainstorming sessions among participant groups, followed by concrete actions or practical activities related to community empowerment materials. The result of the community service activities were consistent with the predetermined plan, as village governments and community representatives demonstrated positive responses and high levels of enthusiasm for the training, resulting in significant improvements in participants’ knowledge, attitudes, and skills.